THE EFFECT OF JOGGING AS INTENSITY AEROBIC EXERCISE ON SHORT-TERM MEMORY AT NURSING SCIENCE STUDY PROGRAM FACULTY OF HEALTH SCIENCE INSTITUT KESEHATAN SUMATERA UTARA IN 2022 - Martina Evlyn Romauli Hutahaean; Sain Jans Melvin Hulu (Health Notions, 2023)
Background: Memory is influenced by very complex factors such as physical activity or exercise. Memory has been shown correlated by physical activity. Jogging is an aerobic exercise has a significant effect on health. The purpose of this study was to determine the effect of jogging as a moderate-intensity aerobic exercise on short-term memory in students of the Nursing Science Study Program, Faculty of Health Sciences, Institut Kesehatan Sumatera Utara. Methods: This research is a quasi experiment using 15 people control group and 15 people experimental groups with random sampling technique. Experimental group jogging for 30 minutes in 7 days. The data were tested using paired-sample t-test. To measure short-term memory using Scenery Picture Memory Test (SPMT). Results: The results showed that there was an effect of jogging as a moderate-intensity aerobic exercise on short-term memory with p = 0.000 (sig < 0.05). Conclusion: There is an effect of jogging as a moderate-intensity aerobic exercise on the short-term memory of nursing students at Faculty of Health Sciences,Institut Kesehatan Sumatera Utara in 2022.